STUDY CONSIDERATIONS ON THE FRETTING PHENOMENON FOR LAMELLAR SPRINGS - Stefan GHIMISI (Fiabilitate şi Durabilitate)
Fretting regimes were first mapped by Vingsbo. In a similar way, three fretting regimes will be considered: stick regime, slip regime and mixed regime. The mixed regime was made up of initial gross slip followed by partial slip condition after a few hundred cycles. For the study of the fretting phenomenon in case of elastics assemblages spring slides with multiple sheets, I used the experimental stall. On the rigid support the elastic lamella is assembling through the agency of the superior plate and of the screws. The elastic lamella oscillates because of the rod crank mechanism with eccentric. This mechanism is auctioned with the electrical engine assuring the necessary conditions for producing the fretting phenomenon